The Economic theory of agrarian institutions - Bardhan, Pranab K. (Clarendon Press ; Oxford University Press, 1989)
This volume contains a series of essays which aims to show how some of the tools of advanced economic theory can usefully contribute to an understanding of how institutions operate. In particular, such techniques can be applied to the study of institutions within poor agrarian economies.